(3GdCQL GdeScj hGdJGQjN Gdecjs - (3YHO GdbGOQ Hf eMeO Hf jMji Hf ecQe Hf eMH GdOjf GdWHQj Gdecj GdMSjfj ,eMjj GdOjf,J (B1033 (3g` s ((3UGdM Hf MSjf GdOYLi s)
(3ChdgG (B:s
(3jG eZOb SMGFH GdfYe Ydi bdhH SGcfi MQec Gdeci CeG HYO , aEf GdYdhe HCSQgG JdHS KjGH GdYXeI hGdLdGdI Ke UQaJ GdgeI ddbjGe HNOeJi GdJOQjS hGdEaJGA ai ZVhf gPg GdeOI UfaJ cJHkG YOjOI s
(3BNQgG (B:s
(3JfJgi HGdHGH GdSGHY ai hdGI ecI ai GdESdGe ZjQ GdSGOI GdCTQGa , Ydi MQha GdeYLe , eY JbOje ef ETJgQ HcfjJg , Hbhdg (B: (3PcQ GHf GdCKjQ Cfg hdjgG ai SfI EMOi hSHYjf heFJjf hOGeJ hdGjI Gdedc GdeSYhO Edi Cf eGJ ai SfI SJ hYTQjf hSJ eFI gPG BNs
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS MOjK ddehVhYGJs
(3CKHJfG GdYfhGf GdehLhO ai OGNd GdebOeIs
(3hJHY Pdc HQhcdeGf (B2/496 (3hde fKHJ eG ai UaMI GdYfhGf s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdJGQjNs